El esquema de Kohlberg revisado: R. S. Peters y la educación moral temprana - Beatriz FERNÁNDEZ HERRERO (Teoría de la Educación: Revista Interuniversitaria, 2009)
1) For his writer, it is not possible to establish a split between reason and passion, since the affectionate aspects of morals are closely linked to the use or reason: one's own reason of assumed moral concepts forms an affectionate reply to other people in society, defined as social feeling or altruism. 2) As far as the theme of contents, Peters establishes his proposal by replying to the following questions: A. WHY WORRY ABOUT THE CONTENTS? The author gives two types of reason: social reason: not all adults évolue towards superior states, many remain in the conventional state, in which it is essential to possess moral contents by which to be guided. Individual reason: learning of the contents is a pre-requisite to the application of rules in a autonomous manner. B. WHAT TYPE OF CONTENTS MUST BE TAUGTH? In reply. Peters elaborates a list of «basic rules», justifiable under any social situation, which along whith principles will constitute the contents of moral education, since according to the author, they are appropriate for whatever form social life the individuals could find. C. How SHOULD THE CONTENTS BE TAUGHT? Peters answers this in a blunt manner: in watever way that may contribute to the children learning rules, taking care not to dull their capacity for developing an independent attitude oppossing them. And as yet the techniques of cognitive stimulation cannot be used whith small children, in the preconventional and conventional states, the author believes that one must employ some form of «instruction». In short, it can be said that the legitimation of Peters' proposal centres on his consideration of morales as actions, which implies the fact that the child is an agent before being a conscious agent, which allows him to express a series of interrogatives as a way of justification of his support of the teaching in early moral education, since his objective must be not so much the development of «forms» and «models» of reasoning, but rather the improvement of behaviour and moral actions of the subject, paying attention to the worry «How to succeed in making the pupils want to become moral?», a worry that must extend to the educational process from the begining, since the ultimate idea of Peters' system is that early moral education is a task that cannot be given up